PELAKSANAAN HAK KONSTITUSIONAL NARAPIDANA UNTUK MEMILIH PADA PILKADA SERENTAK YANG DAERAHNYA BELUM MEMILIKI LAPAS - ZAHRATUL’AIN TAUFIK; DENI HARTAWAN; PUTRI RAODAH (GANEC SWARA, 2024)
The purpose of this writing is to know and understand the implementation of the constitutional rights of prisoners to vote in simultaneous regional elections whose regions do not yet have prisons. It is known that constitutional rights are rights owned by every citizen. These constitutional rights are not limited only because a citizen becomes a prisoner or a person who is serving a sentence for committing a criminal offense. The existence of prisoners detained in detention centers outside the electoral districts is often missed in the process of updating voter data conducted by the KPU, so that so far the voting rights possessed by these prisoners have never been used properly. Problems related to the constitutional rights of prisoners related to the right to vote in Pilkada occur in several regions in Indonesia, one of which is in North Lombok Regency, West Nusa Tenggara Province. This paper is then conducted by collecting and reviewing literature legal materials sourced from various sources of literature, with a Legislative Approach approach that results in invitations and Conceptual Approaches, then analyzed with descriptive analysis methods. The implementation of Regional Head Elections for prisoners in the North Lombok area cannot be carried out, because the KPU as the election organizer does not provide polling stations for prisoners in North Lombok which makes the constitutional rights of prisoners not implemented